Distribution velocity in wine retailing - Martin Hirche; Simone Loose; Larry Lockshin; Magda Nenycz-Thiel (Wine Economics and Policy)
Little is known about the relationship between distribution and market share in the wine category. Understanding the influences of product and distribution characteristics at the SKU-level and incorporating them into marketing strategy and planning has important managerial and academic implications. Sales of 3,524 wine SKUs across 4,218 stores in 4 states in the US over one year of observation are analyzed. We use an established distribution velocity model (Reibstein & Farris 1995) to estimate the relationship between distribution and market share. We then use the market share deviations from the expected values and apply a secondary robust regression to investigate possible relationships between various product- and distribution characteristics and those market share deviations. The results show that the distribution velocity in wine retailing is convex and increasing, in line with previous findings for other consumer-packaged goods in the marketing literature. Beyond distribution breadth, we find that overall parent brand performance (above), unit price (above), packaging type (above), country-of-origin, grape variety, sales consistency (above) and store specialization (below) are associated with above or below expected market share of wine SKUs.